Les objets techniques au prisme du cycle hydrosocial : renouveaux théoriques et empiriques - Marie-Anne Germaine; David Blanchon; Élise Temple-Boyer; Rhoda Fofack-Garcia (Développement Durable et Territoires)
This special issue entitled « Technical objects at the prism of hydrosocial cycle : new theoretical and empirical approaches » presents new insights concerning water-society relations in social sciences. It is characterized by interdisciplinary approaches and engages with two main theoretical frameworks : science and technology studies and political ecology. Both are indeed mobilized in order to deepen the analysis of the dialectical relation between technical objects and hydrosocial systems, by using the concept of hydrosocial cycle. Our aim is to explain how « infrastructure » and « apparatus » forge and transform water-society interrelations, reshape them and modify their functioning. But also how the hydrosocial cycle, in return, sets out particular forms of infrastructure and apparatus. This paper firstly introduces the theoretical and epistemological debates linked to this special issue. And then it presents the thirteen papers gathered in this special issue, which, based on empirical studies, offer different uses of hydrosocial cycle approach to investigate water/society dialectical relations.